Model Manajemen Pembangunan Berkelanjutan Berbasis Good Governance dalam Mewujudkan Kesejahteraan Masyarakat di Indonesia - Sabri Sabri; Eka Febrianti; Asnah Asnah; Rika Novita Sari (Indo Green Journal, 2026)
Sustainable development has become a paradigm that emphasizes balancing economic growth, social equity, and environmental sustainability to improve community welfare. The success of development depends not only on the availability of resources but also on the quality of governance. This study aims to analyze the role of Good Governance in supporting sustainable development and to formulate a conceptual model integrating governance, digital transformation, and cross-sector collaboration to enhance community welfare in Indonesia. This study employed a qualitative approach using the Systematic Literature Review (SLR) method to identify, select, evaluate, and synthesize relevant scientific articles, books, and policy documents. Data were analyzed using content analysis to identify relationships among concepts and develop a conceptual framework. The findings indicate that the implementation of Good Governance principles, including transparency, accountability, public participation, effectiveness, efficiency, and the rule of law, significantly improves public service quality, strengthens public trust, encourages investment, and promotes sustainable economic growth. Furthermore, Digital Government enhances bureaucratic efficiency, transparency, and public service accessibility, while Collaborative Governance strengthens collaboration among government, the private sector, academia, the media, and society in achieving sustainable development goals. Based on theoretical synthesis and previous studies, this research proposes the Sustainable Development Governance Model (SDGM) as its novelty, integrating Good Governance, Digital Government, Collaborative Governance, and Sustainable Development into a comprehensive conceptual framework. The proposed model is expected to advance development management theory and provide practical policy recommendations to achieve sustainable community welfare in Indonesia